"...Disse gutta som selv liksom har vokst opp av landskapet." – Arne Skouen og hans okkupasjonsdramaer - Sørensen, Tonje Haugland (Nordlit, 2012)
Arne Skouen is often heralded as one of the clearest auteurs in Norwegian cinema, and his films about the German Occupation of Norway, 1940-45, are among the most successful and renowned within the Norwegian war film genre. This reading of these four films postulate, that within the framework of the cultural memory of the Second World War II, Skouens four war films offer a coherent and moral reflection about the war time narratives.
Keywords: Memory; Arne Skouen; World War II; War film